2002
DOI: 10.1093/milmed/167.10.801
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Ametropia in Ugandan Soldiers

Abstract: A U.S. Army Optometry team was dispatched as part of the Africa Crisis Initiative to Uganda to provide vision care to a battalion-size task force of the Ugandan Army. Their mission was to ensure vision readiness of the unit and to promote humanitarian good will. Of the 692 soldiers refracted, 117 required spectacle correction to be vision ready. One hundred one records were available to be examined. The distribution of ametropia among this population is consistent with other studies of Third World countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…The distribution of refractive error by type concurs with reports from around the world including Europe [1,2,7,11,12], Asia [9] and Africa [13]. Myopia was the most common refractive anomaly, with a higher prevalence found in more educated populations, similar to other reported studies [9,11,12].…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The distribution of refractive error by type concurs with reports from around the world including Europe [1,2,7,11,12], Asia [9] and Africa [13]. Myopia was the most common refractive anomaly, with a higher prevalence found in more educated populations, similar to other reported studies [9,11,12].…”
Section: Discussionsupporting
confidence: 89%
“…This information was not available from existing reports from Africa [6,13] as they failed to report on the vision status of their study subjects. Spherical refractive errors and anterior segment disorders were the most common ophthalmic disorders and these have implications for needs-based and costeffective provision of eye care services.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…ulation. Different evaluations on military individuals and army arrival volunteers have shown that myopia is more frequent than hyperopia in different parts of the world (31)(32)(33)(34)(35). The prevalence of hyperopia (19.6%) was less than that of myopia (37.7%) in Swedish military recruits (31).…”
Section: Introductionmentioning
confidence: 99%